Investigational parathyroid hormone receptor analogs for the treatment of osteoporosis. (February 2015) - Polyzos, Stergios A; Makras, Polyzois; Efstathiadou, Zoe; Anastasilakis, Athanasios D
<x xml:space="preserve">Abstract</x> Introduction: Intermittent parathyroid hormone (PTH) administration, acting through multiple signaling pathways, exerts an osteoanabolic effect on the skeleton that surpasses the effect of other antiosteoporotic agents. However, its efficacy is limited by the coupling effect and relatively common adverse events. Thus, the development of more sophisticated PTH receptor analogs seems imperative. Areas covered: In this review, the authors summarize the role of PTH signaling pathway in bone remodeling. The authors also summarize investigational analogs targeting this pathway, which may be potential treatments for osteoporosis. Expert opinion: β-arrestins are multifunctional cytoplasmic molecules that are decisive for regulating intracellular PTH signaling. Recently, in preclinical studies, arrestin analogs have achieved the anabolic bone effect of PTH without an accompanying increase in bone resorption. However, it is not yet known whether these analogs have adverse effects and there are no clinical data for their efficacy to date. On the other hand, several molecules derived either from PTH and PTH-related protein (PTHrP) molecules have been developed. Alternative routes of PTH 1 – 34 delivery (oral, transdermal), the PTH analog ostabolin and the N-terminal PTHrP analogs PTHrP 1 – 36 and abaloparatide, have recently been or are currently being tested in clinical trials and are more likely to become available for use in the near future.